Molecular characteristics, biofilm-forming abilities, and quorum sensing molecules in Vibrio parahaemolyticus strains isolated from marine and clinical environments in Korea. Issue 5 (28th May 2017) - Mizan, Md. Furkanur Rahaman; Bang, Hyeon-Jo; Sadekuzzaman, Mohammad; Lee, Nari; Kim, Tae-Jo; Ha, Sang-Do
Abstract: Vibrio parahaemolyticus is an inhabitant of marine and estuarine environments and causes seafood-borne gastroenteritis in humans. In this study, an UltraFast LabChip Real-Time PCR assay was evaluated for rapid detection and quantification of pathogenic V. parahaemolyticus isolates. Escherichia coli and Vibrio harveyi were used as negative controls. Twenty-six tdh -positive, biofilm-producing V. parahaemolyticus isolates were analyzed by repetitive extragenic palindromic-polymerase chain reaction (REP-PCR). REP-PCR analysis showed that the majority of the V. parahaemolyticus isolates originated from seafood and that clinical specimens formed two major clusters at 92.8% and 32% similarity levels. The presence and quantification of Autoinducer-2 was carried out using high-performance liquid chromatography with fluorescence detection (HPLC-FLD) after derivatization of Autoinducer-2 with 2, 3-diaminonaphthalene. The presence of tdh -positive V. parahaemolyticus in marine samples highlights the need for constant environmental monitoring to protect public health.